1982
DOI: 10.1111/j.1365-2125.1982.tb02040.x
|View full text |Cite
|
Sign up to set email alerts
|

A placebo controlled study of the cardiovascular effects of fluvoxamine and clovoxamine in human volunteers.

Abstract: 1 Fluvoxamine and clovoxamine, two new potential antidepressants were given to 27 healthy male volunteers in a double‐blind, placebo controlled, three‐way crossover study. 2 Neither compound affected the electrical intervals of 24 h ambulant electrocardiographic monitoring with the exception of a small increase in R‐R interval. 3 There were no changes in blood pressure measurements. 4 The only notable unwanted symptom was nausea for both fluvoxamine and clovoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Its elimination half-life measured from serum averages G I 0 hours in man, being in depressive patients somewhat longer than in healthy volunteers (Bradford 1984). Clovoxamine in doses up to 360 mg daily has been well tolerated by healthy subjects (Bradford 1984;Robinson & Doogan 1982). Pharmaco-EEG data suggests that single oral doses (SCrlZS mg) of clovoxamine show an antidepressant profile of action, whereas lower doses up to 50 mg exert psychostimulant effects (Bradford 1984;Saletu et al 1980).…”
mentioning
confidence: 99%
“…Its elimination half-life measured from serum averages G I 0 hours in man, being in depressive patients somewhat longer than in healthy volunteers (Bradford 1984). Clovoxamine in doses up to 360 mg daily has been well tolerated by healthy subjects (Bradford 1984;Robinson & Doogan 1982). Pharmaco-EEG data suggests that single oral doses (SCrlZS mg) of clovoxamine show an antidepressant profile of action, whereas lower doses up to 50 mg exert psychostimulant effects (Bradford 1984;Saletu et al 1980).…”
mentioning
confidence: 99%
“…Only Robinson & Doogan reported that FLV slightly prolonged QT intervals but not QTc intervals in humans. 7) In this study, the QTc-prolonging potency (K) of IMI was 1.7-fold higher than that of FLV. However, the therapeutic concentrations of IMI and FLV should be taken into consideration to compare the clinical arrhythmogenic risks of these drugs in clinical settings.…”
Section: Discussionmentioning
confidence: 55%
“…Robinson & Doogan investigated cardiovascular effects of FLV at ordinary dosages (150-300 mg/d) in healthy subjects, and found that the QT interval was slightly prolonged (11-13 ms) by FLV while the QTc interval (QT interval corrected by heart rate) was unaffected because bradycardia was simultaneously induced. 7) However, they did not analyze plasma concentration of FLV, so the relationship between plasma FLV concentration and QT prolongation remains unclear. Wouters and Deiman have reported the arrhythmogenic effects of FLV under toxic concentration in comparison with mianserin and amitriptyline in conscious rabbits.…”
mentioning
confidence: 99%
“…Meanwhile, fluvoxamine decreased the total peripheral resistance, leading to the hypotensive action. Although in vitro vasodilator effect of fluvoxamine has not been reported, the hypotensive action has been observed in patients (de Wilde et al, 1983;de Wilde and Doogon, 1982;Granfors et al, 2004;Guelfi et al, 1983;Rodriguez de la Torre et al, 2001), which was not detected in dogs, cats (Roos, 1983) or healthy human volunteers (Robinson and Doogan, 1982). Importantly, fluvoxamine increased the LVEDP in a dose-related manner; however, the maximum value was 13 ± 1 mmHg at 10 min after the high dose, which still remained within a physiological range.…”
Section: Cardiohemodynamic Effectsmentioning
confidence: 95%